2011
DOI: 10.1534/genetics.110.120675
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling of Host–Symbiont–Phage Coadaptations Following Transfer Between Insect Species

Abstract: Transferring endosymbiotic bacteria between different host species can perturb the coordinated regulation of the host and bacterial genomes. Here we use the most common maternally transmitted bacteria, Wolbachia pipientis, to test the consequences of host genetic background on infection densities and the processes underlying those changes in the parasitoid wasp genus Nasonia. Introgressing the genome of Nasonia giraulti into the infected cytoplasm of N. vitripennis causes a two-order-of-magnitude increase in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 85 publications
4
54
0
1
Order By: Relevance
“…In the D. paulistorum species complex, backgrounds from inter-semispecies hybrids negatively influence host fitness by boosting Wolbachia -titer (Miller et al, 2010). Furthermore a twofold titer increase of native Wolbachia was reported recently in the F1 hybrids between closely related parasitoid wasps of the genus Nasonia (Chafee et al, 2011). Here we generated hybrids between members of the Glossina morsitans group and assessed their Wolbachia -infection titer in comparison to the corresponding parental generation.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…In the D. paulistorum species complex, backgrounds from inter-semispecies hybrids negatively influence host fitness by boosting Wolbachia -titer (Miller et al, 2010). Furthermore a twofold titer increase of native Wolbachia was reported recently in the F1 hybrids between closely related parasitoid wasps of the genus Nasonia (Chafee et al, 2011). Here we generated hybrids between members of the Glossina morsitans group and assessed their Wolbachia -infection titer in comparison to the corresponding parental generation.…”
Section: Resultssupporting
confidence: 52%
“…In the species cluster D. paulistorum , hybrid backgrounds negatively influence host fitness by a massive increase of Wolbachia -infection (Miller et al, 2010). Another recent study demonstrated a twofold titer increase of native Wolbachia accompanied by proliferation into somatic host tissue in hybrids between closely related parasitoid wasps of the genus Nasonia (Chafee et al, 2011). In addition, Login et al (2011) have recently shown that in a beetle host from the genus Sitophilus the load of its primary endosymbiont SPE is strictly regulated by the expression of the host antimicrobial peptide Coleoptericin-A (ColA).…”
Section: Discussionmentioning
confidence: 99%
“…Unidirectional incompatibility in N. vitripennis is strongly influenced by the density of Wolbachia in the male relative to that of the female and has been confirmed by multiple reports involving the same strains utilized in these experiments [8], [23]. Since temperature exposure affects Wolbachia densities in all cold treatments and in the egg heat treatment, we further explored this relationship by comparing the density of Wolbachia required to induce CI at different treatment stages relative to the control 25 C temperature.…”
Section: Resultsmentioning
confidence: 67%
“…Interestingly, altering Wolbachia environmental factors does not abolish this three-way interaction. Introgression to move the w VitA strain from its native host into a related species of wasp, N. giraulti increased Wolbachia load, decreased WO densities, and increased CI [41], while rearing insects at temperature extremes had the opposite effect [42]. In w Pip-infected Culex pipiens mosquitoes under conditions where WO is not lytic, this correlation is not seen [43].…”
Section: Involvement Of Wo In Reproductive Parasitismmentioning
confidence: 99%